Microstructural analysis of collagen and elastin fibres in the kangaroo articular cartilage reveals a structural divergence depending on its local mechanical environment - He, Bo; Wu, Jianping; Chim, Shek Man; Xu, Jiake; Kirk, Brett (Elsevier, 2013)
Objective: To assess the microstructure of the collagen and elastin fibres in articular cartilage under different natural mechanical loading conditions and determine the relationship between the microstructure of collagen and its mechanical environment. Method: Articular cartilage specimens were collected from the load bearing regions of the medial femoral condyle and the medial distal humerus of adult kangaroos. The microstructure of collagen and elastin fibres of these specimens was studied using laser scanning confocal microscopy (LSCM) and the orientation and texture features of the collagen were analysed using ImageJ. Results: A zonal arrangement of collagen was found in kangaroo articular cartilage: the collagen fibres aligned parallel to the surface in the superficial zone and ran perpendicular in the deep zone. Compared with the distal humerus, the collagen in the femoral condyle was less isotropic and more clearly oriented, especially in the superficial and deep zones. The collagen in the femoral condyle was highly heterogeneous, less linear and more complex. Elastin fibres were found mainly in the superficial zone of the articular cartilage of both femoral condyle and distal humerus. Conclusions: The present study demonstrates that the collagen structure and texture of kangaroo articular cartilage is joint-dependent. This finding emphasizes the effects of loading on collagen development and suggests that articular cartilage with high biochemical and biomechanical qualities could be achieved by optimizing joint loading, which may benefit cartilage tissue engineering and prevention of joint injury. The existence of elastin fibres in articular cartilage could have important functional implications.